2022
DOI: 10.3390/clinpract12040057
|View full text |Cite
|
Sign up to set email alerts
|

Association between Anemia and New-Onset Atrial Fibrillation in Critically Ill Patients in the Intensive Care Unit: A Retrospective Cohort Analysis

Abstract: New-onset atrial fibrillation (NOAF) is one of the leading causes of morbidity and mortality, especially in older patients in the intensive care unit (ICU). Although many comorbidities are associated with NOAF, the effect of anemia on the onset of atrial fibrillation is still unknown. This study aimed to test the hypothesis that anemia is associated with an increased risk of developing NOAF in critically ill patients in intensive care. We performed a retrospective analysis of critically ill patients who underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
4
0
1
Order By: Relevance
“…The mentioned study determined a stimulatory cut-off value for the incidence of NOAF with Hb level of 9.96 g/dL. [8] Another large perspective cohort study from Japan followed up a cohort of 132,250 Japanese patients for a mean period of 13.8 years. They reached a conclusion that anemia is associated with higher incidence of AF.…”
Section: Discussionmentioning
confidence: 99%
“…The mentioned study determined a stimulatory cut-off value for the incidence of NOAF with Hb level of 9.96 g/dL. [8] Another large perspective cohort study from Japan followed up a cohort of 132,250 Japanese patients for a mean period of 13.8 years. They reached a conclusion that anemia is associated with higher incidence of AF.…”
Section: Discussionmentioning
confidence: 99%
“…Anemia has a high prevalence in the US 12 and it is associated with poor outcomes in heart diseases due to its hyperdynamic state [13][14][15][16] . Although there are data on the relation between anemia and heart failure and atrial fibrillation [7][8][9] , its relation to ventricular tachycardia lack evidence. In this study, authors used the national inpatient sample from 2016 to 2020 to analyze the difference in outcomes in patients with a primary diagnosis of ventricular tachycardia and anemia compared with the general population.…”
Section: Discussionmentioning
confidence: 99%
“…As such, the imperative nature of discerning the risks correlated with this pathological condition is clear. Anemia has been demonstrated to affect outcomes of atrial fibrillation 7,8,9 and studies showed its association with supraventricular tachycardia 10 . Anemia is also known to increase cardiovascular morbidity and mortality 11 .…”
Section: Introductionmentioning
confidence: 99%
“…При этом было определено пороговое значение уровня гемоглобина для развития впервые возникшей ФП -96,4 г/л. Таким образом, была подтверждена гипотеза о том, что наличие анемии ассоциировано с повышенным риском развития ФП у пациентов, нуждающихся в лечении в отделении интенсивной терапии [32].…”
Section: фибрилляция предсердий анемияunclassified